Early childhood education : a constructivist perspective - Branscombe, N. Amanda; Castle, Kathryn; Dorsey, Anne G. (Boston : Houghton Mifflin, 2000)
Joining a community of learners. Getting information and support. Observing children's development in early childhood education. Children as sense makers. Views of children over time. Exploring the lives of young children and families...
Keywords: Education; Early childhood education; Constructivism; Early childhood education -- United States; Constructivism (Education) -- United States